Effect of training status on Adiponectin concentrations - Bouassida, A.; Lakhdar, N.; Ben Saad, H.; Zaouali, M.; Zbidi, A.; Tabka, Z. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Several studies exploring the effects of acute exercise on adiponectin concentration have resulted in conflicting results (Simpson and Singh, 2008). Jurimae et al., (2005) and Jurimae et al., (2006) showed delayed increases (after 30 min) in adiponectin concentrations, respectively following maximal exercise and following a constant intensity exercise performed by trained rowers. The purpose of this investigation was to analyse the effect of sub-maximal acute exercise at different intensities on plasma adiponectin and insulin concentrations in trained and untrained subjects. Methods: Seven trained (elite handball players) and eight untrained subjects participated in this study. Subjects performed two submaximal cycling exercises of 20 minutes each: moderate and heavy. The intensity of exercises was respectively at 60% and 80% of maximal oxygen consumption (VO2max). Blood samples were obtained before, at the end, after 30, 60 and 90 min of recovery. Results: Adiponectin concentrations were unchanged after both exercises and during recovery in trained and untrained subjects. Insulin concentrations were significantly lowered (P<0.05 and P<0.01) at the end and during recovery in both protocols and groups. The comparison between groups indicated that trained subjects presented lowered control adiponectin and insulin concentrations than untrained counterparts during the moderate and the heavy exercise: -51.2%, P<0.05 and -44.4% P<0.05, respectively for adiponectin and -35.2%, P<0.05 and -35.2% P<0.05, respectively for insulin. Discussion: In accordance with our results, Kraemer et al., (2003) and Ferguson et al., (2004) reported no significant changes in adiponectin concentrations after respectively, a strenuous intermittent running exercise in well-trained runners and a 60 min sub-maximal aerobic exercise in healthy normal weight males and females. In our study, we supposed that the handball elite players undergo a heavy training that can induce significant changes in adiponectin receptors and explain the lowered control adiponectin levels. Our results suggested that 1) 20 minutes acute aerobic exercises not stimulate the production and the release of adiponectin during 90 minutes recovery in trained and untrained subjects, 2) it appears that adiponectin is not associated with insulin modifications and 3) handball athletes showed significantly lower resting adiponectin and insulin response with respect to untrained subjects. This result is probably the consequence of increased level of receptor expression induced by training.